THE ROLE OF PATIENT SAFETY EDUCATION AND TRAINING IN IMPROVING PATIENT SAFETY - Naomi, Ruth; Bahari, Hasnah (International Journal of Patient Safety and Quality, 2024)
Background Patient safety education and trainings are an important element to promote patient safety culture. The demands on this training for the safety of healthcare staffs and patients are crucial due to the occurrence of preventable medical errors. These review aims to study the types of patient safety education and training that are delivered for the different target audiences as well as identifying the results of the training. Methods This study presents narrative review on literature on patient safety education and training. Peer-reviewed journals and previously published papers were searched using keywords including "patient safety training," "improvement," "outcome," "health care," and "health services". Inclusion criteria for the article include the article written in English and published between 2013 and 2018. We used several journal databases including the Journal of Patient Safety, BMJ, PubMed, BMJ Quality & Safety and Google Scholar.  Results Reviews were done based on previously published papers. The findings revealed that the patient safety education and training are mostly conducted to nursing and medical students as well as trainee and residents. Besides, it was also conducted for anesthesiologists and patients. Typically, mannequin-based demonstrations and trainings are provided for medical students and educators through the workshop for physicians and nurses. In addition, most of the important role in ensuring patient safety is mainly done by nurses followed by the anesthesiologist. Conclusion In regards to patient safety, each department has a specific role in ensuring patient safety culture in a clinical unit. Patient safety education and training must be provided for all levels because they may greatly influence the outcome especially on the attitudes and behavioural changes.